The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.jasms.2005.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral fragmentation of the intravenous anesthetic propofol and structurally related phenols

Abstract: Propofol (2,6-diisopropyl phenol) is a widely used intravenous anesthetic. To define its pharmacokinetics and pharmacodynamics, methods for its quantitation in biological matrixes have been developed, but its pattern of mass spectral fragmentation is unknown. We found that fragmentation of the [M Ϫ H] Ϫ ion (m/z 177) of propofol in both APCI MS/MS and ESI MS/MS involves the stepwise loss of a methyl radical and a hydrogen radical from one isopropyl side chain to give the most intense product ion, [M ϪH Ϫ CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…As in the case of DIC, the halogenated ring was untouched; MS (Paíga et al, 2015), most probably the isobutyl sidechain is hydroxylated. The found fragmentation pathway was similar to that described for alkyl-phenols in (Bajpai et al, 2005). …”
Section: Metabolites Of Nsaidssupporting
confidence: 83%
“…As in the case of DIC, the halogenated ring was untouched; MS (Paíga et al, 2015), most probably the isobutyl sidechain is hydroxylated. The found fragmentation pathway was similar to that described for alkyl-phenols in (Bajpai et al, 2005). …”
Section: Metabolites Of Nsaidssupporting
confidence: 83%
“…The mass spectral fragmentation of propofol and related phenols such as thymol was thoroughly studied by Bajpai et al [14] who used transitions 177.2 → 161.2 and 149.2 → 133.0 for propofol and thymol, respectively. These transitions correspond to the loss of methane by the sequential loss of CH 3 and H radicals.…”
Section: Propofolmentioning
confidence: 99%
“…Recently, Bajpai et al [13] reported the formation of the phenoxide radical anion in a CID experiment. The collision energy employed in their experiment was 30-45 eV, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Sometimes, when competing reaction exit channels were not available, radical species appeared as the fragmentation products. [13] It was also proposed that a lower reverse activation barrier due to aromatic stabilization might kinetically favor the formation of radical fragments. [9] In almost all of the cases, the 'even-electron rule' was violated, the decomposition of evenelectron precursor ions was achieved by highly energetic EI or high-energy collisional activation.…”
Section: Introductionmentioning
confidence: 99%